Assessing The Causes Of Household Abandonment - Resta Relita Munte (Estudiante Law Journal, 2021)
This study aims to determine the causes of household neglect. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach, purposive sampling, and descriptive analysis techniques. The results of this study indicate that the cause of household neglect is influenced by two things, including internal factors and external factors. The internal factors can cause education and psychological instability so that it often violates the provisions of the law and factors from self-awareness.Meanwhile, external factors can come from outside, such as the surrounding environment and the lack of harmonious relations in the household. Domestic neglect can lead to domestic violence. Therefore, the relevant parties, in this case, the institution, should give the mandate to protect women and must be active in campaigning for the anti-domestic violence movement, more specifically neglect in the household.